PENERAPAN MODEL LEARNING CYCLE 5E (LC 5E) UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS VIIIC SMPN 10 TAPUNG KAMPAR - Insan Valentino Wibawanto; Rini Dian Anggraini; Armis ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
ABSTRACT: The Research by the application of 5E learning cycle model of learning has been conducted in order to determine the improvement of student learning outcomes in basic competencies solve systems of linear equations of two variables and create mathematical models of the problems associated with the system of linear equations of two variables. The subject of the research is students of class VIII.c of SMPN 10 Tapung in the first semester academic years 2013/2014. This research is a form of action research conducted in two cycles on two basic competence ( KD ). Results of this study indicate that the learning cycle 7E model to increase the participation of learners in the classroom , resulting in improved achievement of students in the junior high school math class VIII.c SMPN 10 Tapung. This research is a classroom action research with two cycles. Each cycle has four stages, the stages are planning, action, observation and reflection. The results show the activity of teachers and students have done well after doing the action. There was enchanment in the number of students who achieved KKM (minimum criteria of achievement) in formative test at the end of each cycle is compared to the number of students who achieve KKM on base score. Starting from 26,92% increased to 50% and increased to 69,23%. Based on these results, we can conclude that the application of the learning cycle 5E to improve learning process and improve the mathematics learning outcomes of students grade VIII.c SMP Negeri 10 Tapung in the first semester academic year 2013/2014.Keywords : learning cycle 5E model, learning achievement, Classroom action research*) Mahasiswa